Islamic Higher Education Branding in The Coastal Area Perspective of Hermawan Kartajaya’s PDB Triangle Theory - Sholikah, Sholikah; Syukur, Fatah; Junaedi, Mahfud (EDUKASIA, 2021)
This article is a research on brand building strategies in private Islamic colleges in coastal areas, namely the IAINU Tuban and the IAI TABAH Lamongan. The purpose of this study is to analyze the strategies of Islamic colleges in coastal areas in building their institutional brands. This research is a case study using a descriptive qualitative approach. The results of this study are the strategies used by IAINU and IAI TABAH in building a brand in accordance with Hermawan Kertajaya's PDB Triangle strategy: 1) Positioning is clarifying campus icons; 2) Differentiation is making the campus characteristic, IAINU Tuban as a religious social entrepreneur campus and having the character of ahlussunnah wal jama'ah an nahdhiyah. Meanwhile, IAI TABAH Lamongan as a center for the development of Islamic science and competitiveness; 3) Brand is making the motto of each institution. The IAINU Tuban brand is a religious social entrepreneur, and the IAI TABAH brand is superior, religious, competitive.